QUALIFICATION WORK OF STUDENTS OF HISTORICAL OF THE FACULTY OF THE PEDAGOGICAL UNIVERSITY: MODERN APPROACHES TO IMPLEMENTATION (Pedagogy of Higher and Secondary Education, 2008)
The article deals with the specific character of complex qualification project made by History faculty students of pedagogical university.